Adsorption of Cadmium and Nickel from Aqueous Solution Using Chitosan and Chemically Modified Chitosan - Joseph Ifeanyi Uche; Blessing Chika Ehiwario (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2022)
Chitosan was produced by complete deacetylation of chitin from crustacean shells (snail shell). ForrierTransfomInfra-Red Spectroscopy(FTIR) analysis of the unmodified chitosan and Acetic anhydride chitosan were carried out. The FTIR spectrum of unmodified chitosan has strong peaks observed at 3640.58cm-1 and the chemically modified acetic anhydride chitosan at 3278.44cm-1. The two products: chitosan and Acetic Anhydride chitosan were applied for the adsorption of cadmium and Nickel from aqueous solution using a UV-visible Spectrophotometer (model JENWAY 6320D) and their percentage sorption was compared. It was observed that the modified chitosan with Acetic Anhydride, showed good ability for metal ion uptake.The amount Cadmium and Nickel absorbed was found to increase with time.Results also indicate that the adsorption capacity of metal ion increased with temperature. The high percentage adsorptions of the materials are due to the additional functional groups present in the samples. It took about 120 minutes for acetic anhydride modified chitosan to reach equilibrium at which a higher percentage sorption (86.50%) was obtained, while unmodified chitosan gave (82.50%).